Peran Peradilan Agama Dalam Penetapan Ahli Waris Endro Bin Sunarto Berdasarkan Prinsip Hukum Islam - Wahyuni, Silvia Ika Nur; Ambarwati, Mega Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The determination of heirs in Islamic inheritance law in Indonesia is a legal process that balances legal certainty, Sharia-based justice, and the protection of heirs’ rights. Within the jurisdiction of the Religious Courts, this authority is affirmed under Article 49 letter b of Law No. 3 of 2006 as well as the Compilation of Islamic Law (KHI) Articles 171–214, which comprehensively regulate the definition of inheritance, requirements for heirs, disqualifications, and the respective shares of heirs. The presence of KHI demonstrates the harmonization between Sharia principles and national law, making Islamic inheritance law not only a religious norm but also legally binding within the national legal system. Judges of the Religious Courts, in exercising this authority, are expected not only to enforce the formal legal aspects but also to uphold substantive justice oriented toward the maqāṣid al-syarī‘ah. Thus, court rulings serve not only to provide legal certainty but also to ensure fairness, preserve family harmony, and prevent potential disputes over the distribution of the deceased’s estate.